Improving Access to Palliative Care at a VHA Hospital. (April 2021) - Cromwell, Carrie A.; Edwards, Beatrice; March, Alice L.
Objective: Explore veteran-specific factors impacting the acceptance of palliative care services at a Veterans Health Administration hospital. Methods: Prospective, focused one-on-one interviews were conducted with 18 inpatient veterans with an initial consult to receive palliative care services. Domains impacting reception of outpatient palliative care management were evaluated including knowledge deficit, emotional barriers, physical barriers, psychosocial barriers, and physical support. Themes and trends from interview responses were analyzed using a qualitative directed content analysis approach. Results: The following themes were discovered to influence veteran participation in outpatient palliative care: Knowledge Deficit, Environmental Factors, Positive Patient Satisfaction, Openness to Technology, and Resiliency. Characteristics of veterans interviewed included an average age of 71 with an average distance from the hospital of 59 miles. Conclusion: The identification of factors impacting veteran access to palliative care will be used to guide interventions and improve receipt of services. Care of seriously ill veterans may be substantially improved by facilitating access to palliative care.